2020
DOI: 10.1111/ejh.13432
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 infection and treatment with hydroxychloroquine cause severe haemolysis crisis in a patient with glucose‐6‐phosphate dehydrogenase deficiency

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an inherited genetic disorder caused by red cell enzymatic defects and is associated with haemolytic crisis when patients are exposed to oxidative agents (fava beans, drugs, infections).Hydroxychloroquine is suspected to trigger haemolytic crisis in G6PD-deficient patients, and off-label administration of this drug to patients infected with the novel coronavirus (SARS-CoV-2) could cause concern. We report here the first case of severe haemolytic crisis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 5 publications
1
57
0
Order By: Relevance
“…There are some discordances between the text and the figures in the data presented by Beauverd et al 1 In the figure, the lowest hemoglobin (nadir) appears to be 6.5 g/dL on day-7 while the same was mentioned as day-6 in the text. This becomes extremely important when considering the temporal relationship between hydroxychloroquine administration and accentuation of ongoing hemolysis.…”
Section: Doubtful Precipitation Of Hemolysis By Hydroxychloroquine Inmentioning
confidence: 84%
See 1 more Smart Citation
“…There are some discordances between the text and the figures in the data presented by Beauverd et al 1 In the figure, the lowest hemoglobin (nadir) appears to be 6.5 g/dL on day-7 while the same was mentioned as day-6 in the text. This becomes extremely important when considering the temporal relationship between hydroxychloroquine administration and accentuation of ongoing hemolysis.…”
Section: Doubtful Precipitation Of Hemolysis By Hydroxychloroquine Inmentioning
confidence: 84%
“…We read with great interest the recent article by Beauverd et al 1 on an interesting case of severe hemolysis in a patient with COVID-19 treated with hydroxychloroquine. The authors concluded that COVID-19 infection was possibly the initial trigger for hemolysis.…”
Section: Doubtful Precipitation Of Hemolysis By Hydroxychloroquine Inmentioning
confidence: 99%
“…The period of hemolysis could not be co-related with a significant rise in reticulocyte count. The reason could be that a) acute viral infections cause transient aplasia due to direct and indirect damage to the hematopoietic stem and progenitor cells (HSPCs) and the surrounding tissue [ 10 ], b) the hemolysis was mild and transient, c) the patient had underlying B12 deficiency, and d) possible iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, COVID-19 infection poses an important confounding factor here, since the infections are the most common trigger for hemolysis in G6PD-deficiency [4]. In a similar report by Beauverd et al, [8] hemolysis was observed even before starting hydroxychloroquine, in a G6PD-deficient COVID-19 patient [9].…”
mentioning
confidence: 82%